Find the cost of lodging: A resort offers a double room for $87.00. Meals in the restaurant are $9.00 per person for breakfast, $14.00 per person for lunch, and $16.00 per person for dinner. How much would it cost two people to stay in the resort each day?


Answer 1


Step-by-step explanation:

Hotel room = 87.00  a double room means for two people

breakfast = 9.00 X 2 = 18.00

Lunch 14.00 X 2 = 28.00

Dinner 16.00 X 2 = 32.00

add the amounts all together 87 + 18 + 28+ 32 =$165.00 for 2 people

Related Questions

Find the measurement of the numbered angles
Simplify each expression below as much as possible. 6x + 2 - 1 - 4x - 3 - 2x + 2
a nonagon is a nine-sided polygon, if a regular nonagon was rotated about its center point, which of the following angels of rotation would not map the figure onto itself
Find the perimeter and area of the regular polygon. Round answers to the nearest tenth.
A resident of Bayport claims to the City Council that the proportion of Westside residents (1) with income below the poverty level is lower than the proportion of Eastside residents (2) The City Council decides to test this claim by collecting a random sample of resident incomes from the Westside of town and a random sample of resident incomes from the Eastside of town. Seventy-six out of 578 Westside residents had an income below the poverty level. Hundred-and-twelve out of 688 Eastside residents had an income below the poverty Specify the hypotheses. Calculate the value of the test statistic (round to 4 decimal places). Calculate the p-value (round to 4 decimal places).

Find the area of a parallelogram if a base and corresponding altitude have the indicated lengths. Base 1 1/2 feet, altitude 6 inches. Area = sq. ft. ...?


area of a parallelogram = A =base*height

so in this case is just (1½)(6).

first off let's convert the mixed fraction to "improper",

\bf \stackrel{mixed}{1(1)/(2)}\implies \cfrac{1\cdot 2+1}{2}\implies \stackrel{improper}{\cfrac{3}{2}} \n\n\n \cfrac{3}{2}\cdot 6\implies \cfrac{18}{2}\implies 9


3/4 sq. ft.

Step-by-step explanation:

The question is using feet and inches. So, you'd have to convert the 6 inches to feet. How many inches in one foot? 6. So 6=1/2 feet so you do 1 1/2*1/2=3/4

Jack has a summer job caddying at a golf course. Jack earns $120a week. By rounding his weekly income to the nearest hundred
dollars, find a reasonable estimate for his total income during the
12 week summer.

A) $700
B) $800
C) $1200
D) $1700


1200 as you would round it down to 100 a week so you would do 100x12

Suri's age is 4 less than 3 times her cousin's age. Suri is 17 years old. Which method can be used to find c, her cousin's age?



7 years

Step-by-step explanation:

Suri's age=17 years

Her cousin's age =c

Suri's age is 4 less than 3 times her cousin's age

4 less than 3 times her cousin's age means subtract 4 from 3 times her cousin's age

17=3c - 4

Find c which is her cousin's age

Add 4 to both sides

17+4=3c - 4 + 4



Divide both sides by 3




C= 7

Her cousin's age = 7 years


Find and simplify


I have no idea what this question is, any ideas?


What this is asking is for you to plug values into the following function:f(x)=(3x-8)/(6x)

Since the question is asking you to find f(3)-f(1), this is how you work it out:
You take the function;
And plug the numbers indicated in for x;
f(x)=(3x-8)/(6x)\nf(3)=(3(3)-8)/(6(3))\nf(3)=(9-8)/(18)\nf(3)=(1)/(18)\n\nf(1)=(3(1)-8)/(6(1))\nf(1)=(3-8)/(6)\nf(1)=(-5)/(6)\n\nNow\ what\ you\ do\ is\ you\ subract\ f(3)\ and\ f(1).\nf(3)-f(1)\nf(3)-f(1)=(1)/(18)-(-5)/(6)\nf(3)-f(1)=(1)/(18)-(-15)/(18)\nf(3)-f(1)=(1+15)/(18)\nf(3)-f(1)=(16)/(18)=(8)/(9)
So the answer to f(3) - f(1) = (8)/(9)

What does the graph tell us about the humidity in any given location on Earth?




Step-by-step explanation:

Answer: A.) The warmer the air temperature, the greater the humidity.

Step-by-step explanation: This is simply what the graph is conveying. As you can see, the line goes up with water vapor and temperature signifying that when the temperature goes up so does the humidity.

what are the steps for multiplying monomial algebraic terms where they have exponents with like bases



See below.

Step-by-step explanation:


a^m * a^n = a^(m + n)


When multiplying monomials with the same base, write the same base and add the exponents.

Other Questions